ANALISIS DAMPAK RANGKAP JABATAN DI PT. POS INDONESIA MALANG - Rahmaditha, Nisabella Fitria; Roziana Ainul Hidayati (Lembaga Penelitian, Publikasi dan Pengabdian Pada Masyarakat, 2023)
PT Pos Indonesia, a leading postal and courier service company, faces ongoing challenges due to the impact of dual roles on employee performance. Research at PT Pos Indonesia Malang identified that dual roles caused a significant decline in performance. Through qualitative methods and interviews with the HR Manager & Secretarial Manager, as well as the Retail Sales & Outlet Services Manager and Branch Operations Manager, the research illustrated the complexity of managing in- and out-of-office responsibilities that led to suboptimal performance. The results highlight the need for appropriate solutions to improve overall employee performance at PT Pos Indonesia. By focusing on task delegation, new employee recruitment, and judicious mutation, the company can overcome the impact of dual roles and improve efficiency and productivity. In conclusion, the suggested solutions can be the foundation for a more effective strategy in managing dual roles in the work environment of PT Pos Indonesia.